Coaxial electrohydrodynamic printing of core–shell microfibrous scaffolds with layer-specific growth factors release for enthesis regeneration - Lang Bai; Meiguang Xu; Zijie Meng; Zhennan Qiu; Jintao Xiu; Baojun Chen; Qian Han; Qiaonan Liu; Pei He; Nuanyang Wen; Jiankang He; Jing Zhang; et al. (International Journal of Extreme Manufacturing, 2024)
The rotator cuff tear has emerged as a significant global health concern. However, existing therapies fail to fully restore the intricate bone-to-tendon gradients, resulting in compromised biomechanical functionalities of the reconstructed enthesis tissues. Herein, a tri-layered core–shell microfibrous scaffold with layer-specific growth factors (GFs) release is developed using coaxial electrohydrodynamic (EHD) printing for in situ cell recruitment and differentiation to facilitate gradient enthesis tissue repair. Stromal cell-derived factor-1 (SDF-1) is loaded in the shell, while basic fibroblast GF, transforming GF-beta, and bone morphogenetic protein-2 are loaded in the core of the EHD-printed microfibrous scaffolds in a layer-specific manner. Correspondingly, the tri-layered microfibrous scaffolds have a core–shell fiber size of (25.7 ± 5.1) μ m, with a pore size sequentially increasing from (81.5 ± 4.6) μ m to (173.3 ± 6.9) μ m, and to (388.9 ± 6.9 μ m) for the tenogenic, chondrogenic, and osteogenic instructive layers. A rapid release of embedded GFs is observed within the first 2 d, followed by a faster release of SDF-1 and a slightly slower release of differentiation GFs for approximately four weeks. The coaxial EHD-printed microfibrous scaffolds significantly promote stem cell recruitment and direct their differentiation toward tenocyte, chondrocyte, and osteocyte phenotypes in vitro . When implanted in vivo , the tri-layered core–shell microfibrous scaffolds rapidly restored the biomechanical functions and promoted enthesis tissue regeneration with native-like bone-to-tendon gradients. Our findings suggest that the microfibrous scaffolds with layer-specific GFs release may offer a promising clinical solution for enthesis regeneration.